Reminders activate the prefrontal‐medial temporal cortex and attenuate forgetting of event memory. Issue 1 (23rd September 2020) - Sekeres, Melanie J.; Moscovitch, Morris; Winocur, Gordon; Pishdadian, Sara; Nichol, Dan; Grady, Cheryl L.
Abstract: Replicas of an aspect of an experienced event can serve as effective reminders, yet little is known about the neural basis of such reminding effects. Here we examined the neural activity underlying the memory‐enhancing effect of reminders 1 week after encoding of naturalistic film clip events. We used fMRI to determine differences in network activity associated with recently reactivated memories relative to comparably aged, non‐reactivated memories. Reminders were effective in facilitating overall retrieval of memory for film clips, in an all‐or‐none fashion. Prefrontal cortex and hippocampus were activated during both reminders and retrieval. Peak activation in ventro‐lateral prefrontal cortex (vPFC) preceded peak activation in the right hippocampus during the reminders. For film clips that were successfully retrieved after 7 days, pre‐retrieval reminders did not enhance the quality of the retrieved memory or the number of details retrieved, nor did they more strongly engage regions of the recollection network than did successful retrieval of a non‐reminded film clip. These results suggest that reminders prior to retrieval are an effective means of boosting retrieval of otherwise inaccessible episodic events, and that the inability to recall certain events after a delay of a week largely reflects a retrieval deficit, rather than a storage deficit for this information. The results extend other evidence that vPFC drives activation of the hippocampus to facilitate memory retrieval and scene construction, and show that this facilitation also occurs when reminder cues precede successful retrieval attempts. The time course of vPFC‐hippocampal activity during the reminder suggests that reminders may first engage schematic information meditated by vPFC followed by a recollection process mediated by the hippocampus.